2021
DOI: 10.1007/s43762-021-00023-w
|View full text |Cite
|
Sign up to set email alerts
|

Latent factor analysis and measurement on sustainable urban livability in Siliguri Municipal Corporation, West Bengal through EFA and CFA model

Abstract: United Nations’ Sustainable Development Goal targets to make cities and human settlements inclusive, safe, resilient, and sustainable; as it is predicting 95% urban expansion in the next decades. Consequently, urban livability can serve as a useful conceptual and analytical framework to improve the quality of urban life by facilitating the evaluation of the person–environment relationship and leading the improvement without deteriorating the environmental conditions. This present paper aims to identify the dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The findings also revealed that access has a strong correlation with the livability of residents. This result mirrors the studies conducted by Adhikari and Roy (2021), who emphasized that access is the most influential factor on urban livability.…”
Section: Discussionsupporting
confidence: 87%
“…The findings also revealed that access has a strong correlation with the livability of residents. This result mirrors the studies conducted by Adhikari and Roy (2021), who emphasized that access is the most influential factor on urban livability.…”
Section: Discussionsupporting
confidence: 87%
“…Principle component analysis (PCA) is employed to carry out EFA. Later, CFA is carried out to verify the relationship between the manifested variables and latent factors (Adhikari and Roy, 2021). The second part of the analysis is the development of a residential location choice model using multinomial logit regression (MNL).…”
Section: Methodsmentioning
confidence: 99%
“…(2020) concluded that social vulnerability harmed ULQ, while Maclean and Salama (2019) found that cultural heritage sites were important for enhancing ULQ. They suggested that urban planners prioritize the creation of cultural amenities to improve ULQ. Other Factors: Additionally, some studies have examined the impact of other factors on ULQ, including housing (Khaef and Zebardast, 2016; Pan et al ., 2018; Ruengtam, 2017), health (Barreira et al ., 2021; Patil and Sharma, 2022), smart city technologies (Adhikari and Roy, 2021; Al-Qawasmi et al ., 2021; Foguesatto et al ., 2022) and safety and security (Alsaid, 2015; Mamuye and Gotu, 2015). In conclusion, ULQ and urban spaces are important topics extensively studied in recent years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other Factors: Additionally, some studies have examined the impact of other factors on ULQ, including housing (Khaef and Zebardast, 2016; Pan et al ., 2018; Ruengtam, 2017), health (Barreira et al ., 2021; Patil and Sharma, 2022), smart city technologies (Adhikari and Roy, 2021; Al-Qawasmi et al ., 2021; Foguesatto et al ., 2022) and safety and security (Alsaid, 2015; Mamuye and Gotu, 2015). In conclusion, ULQ and urban spaces are important topics extensively studied in recent years.…”
Section: Literature Reviewmentioning
confidence: 99%